Postpartum psychosis-an emergent entity - Kapila, Utkarsha; Cevher, Yaren; Tancil, Cemnur; Parikh, Parinda (International Journal Of Community Medicine And Public Health, 2024)
Postpartum psychosis is a rare mental health disorder. It is an emergency because it develops very rapidly and poses a threat to the life of both mother and her child. It is seen that women who suffer from postpartum psychosis have increased risk of committing suicide after delivery, which is also one of the largest causes of maternal mortality in the first-year post-delivery. A history of mental health disorders is deemed unnecessary in cases of post-partum psychosis as it can develop without any previous psychiatric conditions. In this article, the focus of discussion will be- Causes, Symptoms, Diagnosis of post-partum psychosis, Common treatment modalities and Prognosis of postpartum psychosis. We will also be discussing the relation of postpartum psychosis with other mental health illnesses like bipolar disorder and schizophrenia. This data might help in early detection, intervention, and overall improved outcomes in patients of postpartum psychosis.